In vitro ocular metabolism and bioactivation of ketoconazole in rat, rabbit and human. Issue 2 (April 2017) - Cirello, Amanda L.; Dumouchel, Jennifer L.; Gunduz, Mithat; Dunne, Christine E.; Argikar, Upendra A.
Abstract: Oral ketoconazole is clinically administered for treatment of severe cases for fungal keratitis. Pharmacodynamics and efficacy of oral and topical (ocular) ketoconazole have been explored in rabbit. However, metabolism of ketoconazole in the eye in any species is not well explored in any preclinical species or human. An understanding of ocular drug metabolism in the eye is crucial for ocular therapeutics to facilitate the risk assessment and development of potential drug candidates for the clinic. We aimed to investigate the metabolism of ketoconazole in rat, rabbit and human ocular S9 fractions. Metabolism in liver S9 fractions was also studied for a direct comparison. Eleven putative metabolites were identified in the in vitro incubations. Of these metabolites, six were present in rat ocular S9 whereas eight were present in rabbit and human ocular matrices. Metabolic pathways in rabbit and human ocular fractions suggested the formation of reactive intermediates in rabbit and human liver and ocular S9 incubations, which was confirmed with trapping studies. Herein, we report eight human ocular metabolites of ketoconazole for the first time. To the best of our knowledge, this is the first report of ocular metabolic pathways and ocular bioactivation of ketoconazole in preclinical species and human. Graphical abstract: